Exploring Non-Physical Work Environments and Performance: A Case Study of PPNPN Government Employees in Aviation Education - Silvia, Maulana Anifa; Harianto, B.B; Mochklas, Mochamad (East Asian Journal of Multidisciplinary Research, 2024)
This research investigates the impact of non-physical working environments on the performance of Non-Civil Servant government employees at the Aviation Education. Utilizing both t-test and F-test analyses, the study reveals significant findings. The t-test results indicate a calculated t-value of 8.020 with Sig < α (0.029 < 0.05), demonstrating the significance of coefficient β2. At a 95% confidence level, df (n – k = 50 – 2) = 48, where the t-table value is 1.677, suggesting a partially significant effect of the Non-Physical Work Environment variable on employee performance. Moreover, the F-test results show Sig < α (0.000 < 0.05), confirming the significance of coefficient β. With an F-count of 64.313 and utilizing a 95% confidence level, df1 = 1 and df2 = 48, the F-table value is 4.04, indicating a simultaneous significant effect of the Non-Physical Work Environment variable on employee performance. These findings underscore the crucial role of non-physical working environments in enhancing the performance of Non-Civil Servant Government Employees (PPNPN) at the Aviation Education..